THE INFLUENCE AND THE ADVANTAGE OF AMERICAN HIP HOP TO THE RISING ASIAN RAPPERS - Mayza Nisrin Abielah (Universitas Gadjah Mada, 2020)
Cultural imperialism aims at how dominant culture affects other cultures to gain control of certain cultures and create the view that their dominant culture is the center for all countries in the world, which will create uniformity around the world. Therefore, this study will discuss how Asian rappers are influenced by American hip hop culture and how they benefitted from their careers’ success. The theory used in this study is cultural imperialism by John Tomlinson to see the influence of cultural imperialism in American hip hop culture to Asian rappers. The method used in this study is qualitative research by Creswell. The result shows that America’s cultural imperialism influences Asian Rappers by adopting its culture, language, and style of American hip hop. However, its influence is not harmful since the Asian rappers use this to gain more recognition from people, especially in Western, and to be accepted in representing Asian immigrants in the United States.